Nocturnal Polysomnography without Technical Supervision in the Diagnosis of Respiratory Sleep Disorders, Diagnostic Performance of Home and Sleep Laboratory Studies - Angellotti, María Florencia; Grandval, Sofía; Palma, Ileana; Giovini, Vanina; Jaritos, Verónica; Diaz-Lapasini, Gastón; Carnevale, Denise; Nogueira, Juan Facundo (Sleep Science, 2023)
Introduction Unattended Polysomnography (type 2 PSG) is a procedure for the diagnosis of sleep-disordered breathing (SDB). Published evidence on its performance and efficacy is limited. Available studies reveal a high rate of lost records that could limit its application.Objective To assess the efficacy of type 2 PSG and the rate of studies that must be repeated due to critical loss of signals.Methods prospective, descriptive study. Adult patients with suspected SDB were included. Unattended PSG was performed using portable equipment. 75 patients were connected at home and another 75 in the laboratory, without subsequent monitoring. Records were evaluated to determine the percentage of the night with adequate quality for each of the signals, considered as an evaluable signal for = 70% of the total recording time (TRT). The need to repeat the studies was also estimated. Results: 150 patients were recruited; 44% women; age 57.3 ± 15.4 years; BMI 29.4 ± 6.5. EEG and EOG signals were adequate in 149 records. Flow signal by pressure cannula was adequate in 146 and by thermistor in 67.8%. In only one study the signal of both effort bands were inadequate. Oximetry was lost in 4 cases. Ten tracings (6%) met the criteria for repetition; 8 hospital and 2 home.Conclusions Acceptable records were obtained in most unattended PSG studies, both at home and in the sleep laboratory. The rate of repetition of studies due to loss of signal was 6%, with failure in SaO2 or in flow signals being the main cause of the indication.
Keywords: sleep apnea; obstructive; polysomnography; monitoring; ambulatory; home care services; hospital based